Α) i) Στο ορθ. τριγ. ΑΒΓ:εφΒ= β/γ3/4= β/γ3γ= 4β3γ/4= 4β/4β= 3γ/4Π.Θ. στο ορθ. τρ. ΑΒΓ:α^2= β^2 + γ^2α^2= (3γ/4)^2 + γ^2α^2= (9γ^2)/16 + γ^2α^2= (9γ^2)/16 + (16γ^2)/16α^2= (25γ^2)/16α= √(25γ^2)/16α= 5γ/4ii) Στο ορθ. τρ. ΑΒΓ:συνΒ= γ/ασυνΒ= γ / (5γ/4)συνΒ= 4γ/5γσυνΒ= 4/5Στο ορθ. τρ. ΑΒΔ:συνΒ= ΒΔ/γ4/5= ΒΔ/γ4γ= 5ΒΔ4γ/5= 5ΒΔ/5ΒΔ= 4γ/5 εφΒ= ΑΔ/ΒΔ3/4= ΑΔ / 4γ/53/4= 5ΑΔ/4γ12γ= 20ΑΔ12γ/20= 20ΑΔ/20ΑΔ= 3γ/5 iii) ΒΔ= 4γ/5 ΓΔ= α - ΒΔ= 5γ/4 - 4γ/5= 25γ/20 - 16γ/20= 9γ/20 B) (ΑΒΔ)= ΒΔ*ΑΔ/224= (4γ/5 * 3γ/5) / 224= [(12γ^2)/25] /224= (12γ^2)/501200= 12γ^21200/12= (12γ^2)/12γ^2= 100γ= √100γ= 10 cm(ΑΒΓ)= α*ΑΔ/2= (5γ/4*3γ/5)/2= [(5*10/4)*(3*10/5)]/2= (50/4*30/5)/2= (1500/20)/2= 75/2= = 37,5 cm^2 ΜΕΛΙΝΑ Λ.
Συγχαρητήρια Μελίνα. Πολύ ωραία η λύση σου και πολύ προσεχτικά γραμμένη. Η άσκηση του Φεβρουαρίου λύθηκε.
Α) i) Στο ορθ. τριγ. ΑΒΓ:
ΑπάντησηΔιαγραφήεφΒ= β/γ
3/4= β/γ
3γ= 4β
3γ/4= 4β/4
β= 3γ/4
Π.Θ. στο ορθ. τρ. ΑΒΓ:
α^2= β^2 + γ^2
α^2= (3γ/4)^2 + γ^2
α^2= (9γ^2)/16 + γ^2
α^2= (9γ^2)/16 + (16γ^2)/16
α^2= (25γ^2)/16
α= √(25γ^2)/16
α= 5γ/4
ii) Στο ορθ. τρ. ΑΒΓ:
συνΒ= γ/α
συνΒ= γ / (5γ/4)
συνΒ= 4γ/5γ
συνΒ= 4/5
Στο ορθ. τρ. ΑΒΔ:
συνΒ= ΒΔ/γ
4/5= ΒΔ/γ
4γ= 5ΒΔ
4γ/5= 5ΒΔ/5
ΒΔ= 4γ/5
εφΒ= ΑΔ/ΒΔ
3/4= ΑΔ / 4γ/5
3/4= 5ΑΔ/4γ
12γ= 20ΑΔ
12γ/20= 20ΑΔ/20
ΑΔ= 3γ/5
iii) ΒΔ= 4γ/5
ΓΔ= α - ΒΔ= 5γ/4 - 4γ/5= 25γ/20 - 16γ/20= 9γ/20
B) (ΑΒΔ)= ΒΔ*ΑΔ/2
24= (4γ/5 * 3γ/5) / 2
24= [(12γ^2)/25] /2
24= (12γ^2)/50
1200= 12γ^2
1200/12= (12γ^2)/12
γ^2= 100
γ= √100
γ= 10 cm
(ΑΒΓ)= α*ΑΔ/2= (5γ/4*3γ/5)/2= [(5*10/4)*(3*10/5)]/2= (50/4*30/5)/2= (1500/20)/2= 75/2=
= 37,5 cm^2
ΜΕΛΙΝΑ Λ.
Συγχαρητήρια Μελίνα. Πολύ ωραία η λύση σου και πολύ προσεχτικά γραμμένη. Η άσκηση του Φεβρουαρίου λύθηκε.
Διαγραφή